Er3+,Yb3+:YGdSiO5 Crystal as Gain Media for Lasers Emitting in the Spectral Range of 1.5–1.6 µm - K. N. Gorbachenya; A. S. Yasukevich; V. E. Kisel; N. A. Tolstik; A. A. Tarachenko; V. I. Homan; L. K. Pavlovskiy; V. A. Orlovich; E. A. Volkova; V. O. Yapaskurt; N. V. Kuleshov (Приборы и методы измерений)
Solid-state erbium lasers, emitting in the spectral range of 1.5–1.6 µm, are of great interest for several industrial applications. Nowadays the Er:glass is the most widespread laser material for obtaining laser radiation at the wavelength near 1.5 µm. However, the maximal output powers of such lasers are restricted by hundreds of milliwatts because low thermal characteristics of the glass host. By this reason the search for new crystalline hosts doped with erbium ions is the actual task.In this article the investigation results of spectroscopic properties of Er3+,Yb3+:YGdSiO5 (YGSO) crystals are reported. Polarized absorption and luminescence spectra were measured. The lifetimes of energy levels were determined. The excited state absorption spectra were measured. It was shown that excited state absorption band does not overlap with gain band in the range 1.5–1.6 µm. The energy transfer efficiency from ytterbium to erbium ions was estimated. The stimulated emission and gain cross-section spectra for Er3+ ions in YGSO were calculated.